Formation of responsibility and independence as a feature of personality of student youth in the process of educational work higher education institutions - Druhanova, Olena; Kvasova, Katerina; Nalyvaiko, Oleksii (Scientific notes of the pedagogical department, 2022)
The aim of the article is to substantiate the role of the educational environment of higher education institutions, under the influence of which students form a system of principles, values and moral guidelines, rethink existing ways of working and creating new ones. It is proved that an important role in the formation of such an environment is played by systematic educational work, including round tables, curatorial hours, talks with students of diﬀerent courses and other forms and areas. It was found that the key to the correct attitude of students to learning, to further professional and social activities is their awareness of the importance of their initiative, determination, perseverance, demanding and other qualities that contribute to responsibility in action; needs for constant self-improve- ment, self-organization, etc. End-to-end discussion of current issues of education, upbringing, personality formation in general among graduates of senior and junior courses, between students and teachers, creating situations that encourage responsible decision-making, to express student social activity, promote responsibility and independence as personality traits . The article summarizes the methods and means of forming responsibility as an integral quality of personality accumulated by the domestic higher school. This is the humanization of the process of cooperation, the dialogue of learning; organization of socially significant workshops, solving deontological situations, situational exercises; reading special courses; performing tasks of independent work, etc. The role of scientific-pedagogical/assistant practice as a tool for creating and directing opportunities for students of the second (master’s) level of higher education to self-development and self-improvement, to express their own creative activity, freedom of choice, responsibility in specific educational activities. The article proposes curatorial hours for active discussion with students of diﬀerent levels of higher education in order to form their responsibility and independence – «The role of responsibility in human life and society in the context of education», «Leadership in the student environment», Problems of academic integrity in Ukraine and the world, etc.